Analysis of the sensitivity of a vibration-based procedure for structural identification - Auzins, J.P.; Boyko, A.F. (Проблемы прочности, 2006)
We analyze the accuracy of estimation of structural component material properties (elastic modulus, Poisson’s ratio, density, etc.) using the technique for measuring the eigen frequencies of oscillations. The accuracy of frequency estimation using the Fourier method and its influence on the final result are evaluated. Relationships between the errors in the frequency estimation and those in the identified parameters are derived using the meta-model method. Application of the method is illustrated by the example of a shell element with a stiffening rib.